Are We All Playing the Same Game? The Economic Effects of Constitutions Depend on the Degree of Institutionalization - German Caruso; Carlos Scartascini; Mariano Tommasi (Inter-American Development Bank (IDB), 2013)
The understanding of the economic effect of formal institutional rules has progressed substantially in recent decades. These formal analyses have tended to take for granted that institutional arenas such as Congress are the places where decision-making takes place. That is a good approximation in some cases (such as many developed countries today) but not in others. If countries differ in how institutionalized their policymaking is, it is possible that the impact of formal political rules on policy outcomes might depend on that. This paper explores that hypothesis and finds that some important claims regarding the impact of constitutions on policy outcomes do not hold for countries in which institutionalization is low. The findings suggest the need to develop a broader class of policymaking models in which the degree to which decision-making follows 'the rules' is also endogenized.
Keywords: D72; D73; D78; H20; H60; H62; 330